Intensitas bermain judi online meningkat: Bagaimana peranan kontrol diri? - Fitrinanda, Ramadani Dwi; Meiyuntariningsih, Tatik; Ramadhani, Hetti Sari (JIWA: Jurnal Psikologi Indonesia, 2024)
Abstract Play intnsity is th level of how often an individual carries out certain activities based on feelings of enjoyment in the activity being carried out. This research aims to find out whthrr there is a relationship between self-control and the intensity of playing online gambling. Correlational quantitative research method with a total of 99 respondent as online gambling players taken using a purposive sampling technique. The research scale based on Averill’s theory (2010) with a cronbach alpha value of 0,98 and a playing intensity scale based on horrigan’s theory (2002) with a cronbach alpha value of 0,73. The data analysis technique uses Pearson product moment correlation analysis. The research results sho that there is a negative relationship between selfcontrol and the intensity of playing online gambling. Through slf-control, online gambing players can sort out the impacts of actions that are detrimental to themselves so that the intensity of paling online gambling can decrease. Abstrak lntensitas bermain merupakan tingkat seberapa sering individu dalam melakukan kegiatan tertentu yang didasari oleh perasaan senang pada kegiatan yang dilakukan. PeneIitian inii bertujuan untuk mengetahui apakah ada hubungan antara kontroI diridengan intensitas bermain judi online. Metoode peneIitian kuantitatif koreIasionaI dengan jumlah responden sebanyak 99 orang pemain judi online yang diambil dengan teknik purposive sampling. Skala penelitian menggunakan skala kontrol diri disusun berdasarkan teori Averill (2010) dengan nilai cronbach alpha 0,98 dan skala intensitas bermain yang disusun berdasarkan teori Horrigan (2002) dengan nilai cronbach alpha 0,73. Teknik analisis data menggunakan analisis korelasi pearson product moment. Hasil penelitian menunjukkan adanya hubungan negatif antara kontrol diri dengan intensitas bermain judi online. Melalui kontrol diri pemain judi online dapat memilah dampak-dampak perbuatan yang merugikan dirinya sehingga dapat membuat intensitas bermain judi online menurun.